1992
DOI: 10.1177/088626092007001006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault of the Elderly Victim

Abstract: This study evaluated elderly victims of rape and determined the variables affected solely by the patient's age. It was conducted in a non-hospital-based clinic that serves as the primary resource for rape victims in Shelby County, Tennessee. Fifty-three women, 55 years of age or older, were compared with 53 patients aged 18 to 45 who were selected for the control group. The racial composition was similar for both groups. There was no difference in the time interval to examination. Among the elderly, the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
5
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 3 publications
8
61
5
2
Order By: Relevance
“…15 In 28% of older women who are sexually assaulted, injuries sustained to the genital area may be severe enough to warrant surgical repair. 16 As women age, there are physiologic changes in the genital tract that may result in vaginal dryness and thinning of the vaginal mucosa. Additionally, in both men and women, muscle atrophy, osteoporosis, and decreased subcutaneous tissue can be contributing factors to the severity of injury.…”
Section: Sexual Abuse Examinationmentioning
confidence: 99%
“…15 In 28% of older women who are sexually assaulted, injuries sustained to the genital area may be severe enough to warrant surgical repair. 16 As women age, there are physiologic changes in the genital tract that may result in vaginal dryness and thinning of the vaginal mucosa. Additionally, in both men and women, muscle atrophy, osteoporosis, and decreased subcutaneous tissue can be contributing factors to the severity of injury.…”
Section: Sexual Abuse Examinationmentioning
confidence: 99%
“…A majority recognized that social isolation, cognitive impairment, and history of domestic violence in the home increase a person's risk of some forms of elder abuse (Acierno et al, 2010;Choi & Mayer, 2000;Lachs et al, 1997;Post et al, 2010). Over half were also knowledgeable of numerous facts about sexual abuse, including: elderly populations have an increased chance of vaginal or anal tearing (Muram, Miller, & Cutler, 1992), genital trauma, or serious injury (Vierthaler, 2004); reduced cognitive or emotional functioning may increase sexual abuse risk (Cooney, Howard, & Lawlor, 2006); elder sexual abuse survivors are unlikely to report abuse (Vierthaler, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Participants were open to acknowledge the wrongdoing in their behaviour and a need to change, whilst protecting the self as not fully responsible. Muram et al (1992) and Cartwright and Moore (1989) identified availability and vulnerability as key factors in offences against elderly victims in general. The study provides support for these commonalities found in the research in that all the victims lived alone and were attacked in their own home.…”
Section: Discussionmentioning
confidence: 99%
“…In further support of this, Cartwright and Moore (1989) concluded from their retrospective analysis of reported sexual offences, that elderly rape is motivated by anger. Research has also suggested that availability and vulnerability are key factors in why sexual offenders may target elderly victims (Muram et al, 1992;Cartwright & Moore, 1989).…”
mentioning
confidence: 99%